Advanced anaplastic thyroid carcinoma with positive expression of PD-L1 response to immune checkpoint inhibitors: A case report - Shanmin Fan; Yang Yuan; Yanfang Su; Die Sang (SAGE Open Medical Case Reports)
Anaplastic thyroid carcinoma (ATC) is one rare type of thyroid carcinoma without standard systemic treatment for advanced disease. Recent evidence has demonstrated promising efficacy of immune checkpoint inhibitors, particularly those targeting programmed death-1 (PD-1)/programmed death ligand 1 (PD-L1), in a variety of solid tumors. However, there have been no research of immune checkpoint inhibitors plus chemotherapy in ATC. Here, we present the case of a 37-year-old man with metastatic ATC with positive PD-L1 expression, who achieved long-term remission of 34 months after later-line treatment with zimberelimab (a PD-1 inhibitor) and nab-paclitaxel, followed by single-agent zimberelimab maintenance therapy. After three cycles of the combination treatment, the thyroid lesion and the liver metastases shrank dramatically, leading to the best overall response of partial remission. PD-L1 expression may serve as a potential biomarker for tumor response to immune checkpoint inhibitors in ATC. Our review highlights the need for further studies investigating the role of PD-L1 status as biomarker to predict the prognosis of immunotherapy in the treatment of ATC.